2020
DOI: 10.1007/s00066-020-01667-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-neoadjuvant treatment with capecitabine and trastuzumab emtansine in breast cancer patients—sequentially, or better simultaneously?

Abstract: Purpose Following neoadjuvant chemotherapy for breast cancer, postoperative systemic therapy, also called post-neoadjuvant treatment, has been established in defined risk settings. We reviewed the evidence for sequencing of postoperative radiation and chemotherapy, with a focus on a capecitabine and trastuzumab emtansine (T-DM1)-based regimen. Methods A systematic literature search using the PubMed/MEDLINE/Web of Science database was performed. We included prospective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“… 130 , 131 , 132 , 133 , 134 Side effects reported in this setting are minimal (radiation dermatitis, pneumonitis, and cardiac toxicities), and safety has been reported when administrated with concurrent RT in a recent systemic review. 135 …”
Section: Resultsmentioning
confidence: 99%
“… 130 , 131 , 132 , 133 , 134 Side effects reported in this setting are minimal (radiation dermatitis, pneumonitis, and cardiac toxicities), and safety has been reported when administrated with concurrent RT in a recent systemic review. 135 …”
Section: Resultsmentioning
confidence: 99%
“…Data from the randomized controlled KATHERINE and ATEMPT trials demonstrated similar rates of radiotherapy-related toxicity when comparing trastuzumab monotherapy to T-DM1 with concurrent use during radiotherapy [31,33]. Thus, the concurrent use of T-DM1 with adjuvant radiotherapy is considered safe [35].…”
Section: Discussionmentioning
confidence: 96%
“…Zu den Indikationen zur Teilbrustbestrahlung ist im Jahr 2020 eine Leitlinie der DE-GRO veröffentlich wurden [56,57].…”
Section: Auch Das Nicht Brustkrebsspezifischeunclassified